Network-Generative Architecture a net-resilient paradigm for critical information infrastructure - Abes, Pocholo Alfonso M.
In the realm of architectural design for critical information infrastructure, there is a noticeable gap in literature concerning the harmonious integration of human and technological resilience. Existing studies predominantly emphasize the robustness of built environments in withstanding shocks, overlooking the nuanced interplay between human users, non-human equipment, and the surrounding ecological environment within an architectural network. To address this gap, this research adopts an interdisciplinary approach, drawing insights from data center experts and cybersecurity professionals in the Philippines. Conducting interviews with key industry figures and performing site visits to existing data center spaces, this research aims to understand the spatial needs and preferences of critical infrastructure and knowledge workers. The findings from these engagements will be systematically compared to models for resilient spaces, facilitating the adaptation of these models to the unique context of the Philippines. The outcome will serve as the foundation for designing an Information Shelter, integrating a colocation data center and a cybersecurity research and development hub. This research argues that true resilience in critical information infrastructure necessitates a holistic approach encompassing all elements within the architectural network. Guided by Actor-Network Theory, the proposed design concept seeks to establish a net-resilient paradigm, acknowledging the interconnectedness of human, technological, and ecological components. The research contributes to the discourse on spatial design principles crucial for fostering innovation and resilience in the face of evolving threats, emphasizing the need for adaptable and interconnected built environments.